Synthesis and characterization of novel symmetrical and asymmetrical substituted Zn(II) phthalocyanines - Dumrul, Hakan; Yüksel, Fatma (Pergamon-Elsevier Science Ltd, 2013)
In this report, the synthesis and characterization details of symmetrical and asymmetrically substituted zinc phthalocyanines (pcs) were presented. The synthesis of new pc derivatives was achieved by cyclotetramerization reaction of corresponding phthalonitrile or phthalonitrile mixtures in n-pentanol in the presence of Zn(OAc)(2) and strong base. In the cyclotetramerization reactions of 4-tert-butylcarbamatephenoxy)-substituted phthalonitrile derivatives, transcarbamoylation occurred spontaneously by replacement of tert-butyloxy unit of N-protective group (BOC) with n-pentanol solvent, and 4-pentylcarbamatephenoxy-substituted asymmetrically and symmetrical Zn(II)Pcs were obtained as reaction products. New compounds were fully characterized by elemental analysis, IR, NMR, and mass spectra and their photophysical properties were investigated by means of absorption and emission spectroscopy. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Carbamate; Transcarbamoylation; Fluorescence